ARTIFICIAL INTELLIGENCE AND NATIONAL SECURITY: PERSPECTIVE OF THE GLOBAL SOUTH - Srivastava, Kushal (International Journal of Law in Changing World, 2023)
It has been more than sixty years since the concept of Artificial Intelligence (AI) took its initial form. Since then there have been several discussions and debates on AI and its future as the focal point. Today, decades down the line; AI is standing at the door highlighting a paradigm shift of its own. The entire trajectory can also be seen because of an optimistic approach towards the future of technologies that carved the recent times, which we are living in. It can be inferred that the day has come when AI has started operating almost all facets of human life. Such a change possesses drastic potential when the perspective of the global south comes into picture. Apart from mundane activities of humankind, another pertinent aspect of contemporary society is that of national security. Every country of the global south is quite proactive when it comes to strengthening its internal security and countries try to ward off hurdles and mitigate them largely through every possible way. Furthermore, in light of the development and increase in the usage of AI, it is worth pondering on the future of AI in the domain of national security with perspective of the entire domain of the global south. Indeed every concerned government entities like the military of such nations are focusing more on AI based technologies with an objective to enhance their overall capabilities. For instance, the facets of surveillance, cyber security, and venturing towards autonomous equipment are some key areas where nations are focusing on and AI has seen an appropriate enabler towards such cause. Through this review paper, an analytical discussion has been made towards the fact that how the postulate of AI can be used to analyze large stock of data, evaluate the connected patterns, and detect potential security threats. This paper narrows down the discussion to the perspective of the global southern part of the world and analyses the entire situation of AI and its prospective future in the realm of cyber security and national security of the connected nations. The discussion also considered the existence of several concerns with regard to the congruence of AI and national security. By reviewing various existing literature, it projects a discussion and analyzes various pertinent aspect connected to this domain. Eventually, it makes an attempt to put forward suggestions to the question at hand as to whether AI in national security can be seen as a facilitator that can help in strengthening the nation’s internal security or are we overlooking a hurdle that it may entail and is still a far sighted dream.